A SNAP-tagged derivative of HIV-1 - a versatile tool to study virus-cell interactions - Eckhardt, Manon; Anders, Maria; Muranyi, Walter; Heilemann, Mike; Krijnse-Locker, Jacomine; Müller, Barbara (PLOS ONE, 2011)
Fluorescently labeled human immunodeficiency virus (HIV) derivatives, combined with the use of advanced fluorescence microscopy techniques, allow the direct visualization of dynamic events and individual steps in the viral life cycle. HIV proteins tagged with fluorescent proteins (FPs) have been successfully used for live-cell imaging analyses of HIV-cell interactions. However, FPs display limitations with respect to their physicochemical properties, and their maturation kinetics. Furthermore, several independent FP-tagged constructs have to be cloned and characterized in order to obtain spectral variations suitable for multi-color imaging setups. In contrast, the so-called SNAP-tag represents a genetically encoded non-fluorescent tag which mediates specific covalent coupling to fluorescent substrate molecules in a self-labeling reaction. Fusion of the SNAP-tag to the protein of interest allows specific labeling of the fusion protein with a variety of synthetic dyes, thereby offering enhanced flexibility for fluorescence imaging approaches. Here we describe the construction and characterization of the HIV derivative HIVSNAP, which carries the SNAP-tag as an additional domain within the viral structural polyprotein Gag. Introduction of the tag close to the C-terminus of the matrix domain of Gag did not interfere with particle assembly, release or proteolytic virus maturation. The modified virions were infectious and could be propagated in tissue culture, albeit with reduced replication capacity. Insertion of the SNAP domain within Gag allowed specific staining of the viral polyprotein in the context of virus producing cells using a SNAP reactive dye as well as the visualization of individual virions and viral budding sites by stochastic optical reconstruction microscopy. Thus, HIVSNAP represents a versatile tool which expands the possibilities for the analysis of HIV-cell interactions using live cell imaging and sub-diffraction fluorescence microscopy.
Gesehen am 06.04.2022